1985
DOI: 10.1037/0022-3514.49.6.1643
|View full text |Cite
|
Sign up to set email alerts
|

APA presidential addresses: The relation of integrative complexity to historical, professional, and personal factors.

Abstract: The 85 extant presidential addresses of the American Psychological Association (APA) were scored for integrative complexity, a factor denned by the degree of differentiation and integration of dimensions along which information is processed. As in previous studies, complexity was lower when the United States was engaged in a war. This predicted effect of societal stress was not found in times of economic difficulty nor during United States presidential election years. APA presidents who were judged as particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 27 publications
3
38
0
1
Order By: Relevance
“…I might also cite another relevant finding concerning integrative complexity, the factor that discriminates eminent human-science-oriented psychologists from equally eminent naturalscience-oriented psychologists (Suedfeld, 1985). Feist (1994) found that integrative complexity was positively associated with peer-rated eminence for natural scientists, as were total citations received in the professional literature.…”
Section: Dispositional Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…I might also cite another relevant finding concerning integrative complexity, the factor that discriminates eminent human-science-oriented psychologists from equally eminent naturalscience-oriented psychologists (Suedfeld, 1985). Feist (1994) found that integrative complexity was positively associated with peer-rated eminence for natural scientists, as were total citations received in the professional literature.…”
Section: Dispositional Predictorsmentioning
confidence: 99%
“…On a far more limited scale regarding the number of variables investigated was Suedfeld's (1985) content analysis of addresses delivered by presidents of the American Psychological Association. The speeches were scored on integrative complexity: a measure of how many divergent perspectives a person can take into consideration and whether the person can integrate these perspectives into a coherent viewpoint.…”
Section: Dispositional Traitsmentioning
confidence: 99%
“…At the other extreme are those investigators who define the sampling criterion in terms of explicit and objective rules, a practice almost universal in psychometric and historiometric inquiries. The most common of these sampling rules an: (a) nominations by experts in the field (e.g., Baltes, Staudinger, Maercker, & Smith, 1995;Coan, 1973), (b) occupation of special positions, such as political leaders or television news broadcasters (e.g., Mullen et al, 1986;Zweigenhaft, 1975); (c) receipt of major honors, such as Nobel prizes or Olympic gold medals (e.g., Medvec, Madey, & Gilovich, 1995;Suedfeld, 1985;Wertheimer, 1982), and (d) conspicuous representation in archival sources, such as encyclopedias, biographical dictionaries, histories, citation indexes, or obituaries (e.g., Farnsworth, 1969;Harrison, Struthers, & Moore, 1988;Suedfeld & Bluck, 1993). The specific method chosen usually depends on other features of the study, such as the nature of the hypothesis or whether the measures are to be direct or indirect.…”
Section: Samplingmentioning
confidence: 99%
“…Conceptually similar to dialectics is integrative complexity, a construct from social psychology. Both dialectics and integrative complexity involve a readiness for accepting and resolving contradictions as well as an openness to change and uncertainty (Suedfeld, 1985). Research indicates that integrative complexity in political speeches and writing tends to diminish during periods of war or severe hardship (Tetlock, 1988), implying that reductionistic views may be more 'comforting' or acceptable during periods of high stress.…”
mentioning
confidence: 99%